The The Implementation of Universal Design for Learning in English Instruction at an Inclusive Elementary School - Ramadhani Uswatun Khasanah; Fendy Yogha Pratama; Ika Vitasari; Hanan Fakhriya Qonita (International Journal of Learning Reformation in Elementary Education, 2026)
Inclusive education in elementary schools ensures equitable learning opportunities for students with diverse needs; however, instructional practices often assume learner homogeneity. This study investigates the implementation of the Universal Design for Learning (UDL) framework in English language instruction at an inclusive elementary school in Yogyakarta, focusing on the principles of multiple means of engagement, representation, and action and expression. Employing a qualitative case study design, data were collected through in-depth interviews, classroom observations, and document analysis, and examined using an interactive analysis model. The findings indicate that UDL is implemented contextually, particularly in engagement and representation, as teachers utilize game-based learning, participatory activities, and multimodal resources to enhance motivation and accessibility. However, implementation of action and expression remains limited, particularly in assessment practices, which are still largely standardized and dominated by written tests. These findings suggest that UDL implementation remains at an emerging stage, where diverse instructional strategies have not yet been fully aligned with differentiated assessment approaches. This study contributes to the limited literature on UDL in English language teaching in inclusive elementary contexts in Indonesia and highlights the need to strengthen teachers’ competencies in designing flexible and differentiated assessments.